Do Remittances Have A Flip Side ? : A General Equilibrium Analysis of Remittances, Labor Supply Responses, And Policy Options For Jamaica - Bussolo, Maurizio (The World Bank, 2007)
Econometric analysis has established a negative relationship between labor supply and remittances in Jamaica. The authors incorporate this ex-post evidence in a general equilibrium model to investigate economywide effects of increased remittance inflows. In this model, remittances reduce labor force participation by increasing the reservation wages of recipients. This exacerbates the real exchange rate appreciation, hurting Jamaica's export base and small manufacturing import-competing sector. Within the narrow margins of maneuver of a highly indebted government, the authors show that a revenue-neutral policy response of a simultaneous reduction in payroll taxes and increase in sales taxes can effectively counteract these potentially negative effects of remittances